Implementing Newton-Raphson Method Algorithm in 6 Programming Languages’ Solution to Van Der Waals Equation of State - Abdulhalim Musa Abubakar1; Eva Schieferstein; Volodymyr Kutarov; Muhammad Tayyab Bilal; Chantawan Noisri; Bello Iliyasu (Formosa Journal of Computer and Information Science, 2023)
Newton’s method can be implemented for the Van der Waals equation of state (VDW EOS) and its derivatives. Application of programming language in chemical engineering is not new but however limited in practice, as it is not included in the curriculum of students of tertiary institutions across the globe. Finding roots through iteration for the VDW EOS can be described as interesting and simple using C++, FORTRAN, R, MATLAB, Java and Python languages; even though a perfect programming language does not exist. In this work, the coding syntax in the six languages employed to solve parameters in VDW EOS differs in terms of simplicity and user-friendliness. Notwithstanding, all of them proves to be an adaptable software, capable of solving chemical engineering problems leading to nonlinear relations